From Landscapes and Villages to Celebrations and Legends in Rosalía de Castro’s Cantares gallegos - González Godínez, María Berenice (Madrygal. Revista de Estudios Gallegos, 2023)
Cantares gallegos by Rosalía de Castro is a landmark work not only for the aesthetic quality of its poems, but also for the impact of producing a literary book in Galician in the nineteenth century – a development that signaled a revival of letters and culture in this historical language. What stands out in Cantares is the presence of elements characteristic of Galicia interwoven throughout the volume, belonging to the traditions, customs, and folk knowledge of the Galician nation. This article examines references to settlements, music, dance, festivities, religious beliefs, legends, and everyday activities, as well as the recurrent strain of melancholy – features that, although rooted in nineteenth-century settings, remain part of Galician cultural identity. The principal aim of this reading is to demonstrate that Cantares gallegos is not merely a compilation of poetic glosses on popular cantigas, but a journey through Galicia and its ancestral customs.
Keywords: Poetry; Culture; Galicia; Rosalía de Castro; Cantares gallegos